The body in Martin Amis's Experience (2000). Issue 7 (10th November 2017) - Vickers, Neil
ABSTRACT: This paper focuses on the presentation of the body in Martin Amis's memoir Experience (2000) and compares Amis's account of the growth of his mind and body with ideas put forward by writers in the phenomenological and psychoanalytic traditions. Using the ideas of body schema, projective identification and idea of safety, it advances a new conceptual framework for the thinking about the contribution that the body makes to selfhood in autobiography.